TINJAUAN YURIDIS HUKUM WARIS BAGI KHUNSA ATAU BERKELAMIN GANDA DALAM PANDANGAN HUKUM ISLAM - Jauhari, Zaidan (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACK Humans are grouped as male and female and at birth are treated as boys and girls by parents and it is easy to learn gender as adults. However, for a small number of people, the effort to develop a gender identity is a problem. It means multiple sexes.The type of research used by the author is normative or doctrinal juridical law research, the explanation of which is normative legal research, another name is doctrinal legal research which is also referred to as library research or document study.Multiple sexes in Islam are called Khunsa, Khunsa is divided into 2 namely Khunṡa Ghairu musykil (Khunṡa That Is Not Difficult or Clear) and Khunṡa musykil which is very difficult to determine it cannot be known whether he is male or female, because there are no signs that indicate masculine or vague. However, the mujtahids have determined two ways to determine the sex of the khuna, namely from the genitals and examining the signs of maturity. can also be carried out genital surgery whose purpose is repair or refinement.The distribution of inheritance for a khuntsa ghairu muskyil is seen from his status after going through several ways by seeing the first discharge of urine and also from the signs of maturity. The division of the inheritance of a mushkil khuntsa according to the Shafi'i khuntsa school is given the smallest share of the male and female share then the rest of the property is suspended. Keywords: Law of Inheritance.Status.Multiple.